Educating under duress: a sociology of juvenile justice - Cordeiro, Veridiana Domingos (Plural, 2017)
Review of: Sallée, Nicolas. Éduquer sous contrainte: une sociologie de la justice des mineurs. Paris: Éditions de l’EHESS, 2016.